SKIN AVILABLE MASTOID AREA ON THE STAGE OF ITS STRAIN - D.S. Avetikov; D.V. Steblovskii; I.I. Starchenko (Український стоматологічний альманах)
According to the latest statistics in the scientific journals abnormal scarring and negative results of plastic surgery occur in 5-6% of the total. Therefore, an optimal aesthetic scar and maximum results after cosmetic otoplasty are obtained and lower rhytidectomy remains a challenge in plastic and reconstructive surgery and rehabilitation.